Ground bearing concrete slabs specification, design, construction and behaviour - Knapton, John (Thomas Telford, 2003)
Ground bearing concrete floors, industrial concrete hardstandings and concrete highway pavements have not, in the past, been perceived as a single type of structural element and their construction has taken place independently of each other. This title focuses on the issues that are common to them all.